Health Workers Handling Covid-19, Heroes Without Protection? - Sheila Kusuma Wardani Amnesti (Universitas Muhammadiyah Purwokerto, 2021)
In recent months the world has faced a serious case in the form of the Covid-19 pandemic. All work together in order to reduce the number of increasing cases of Covid-19. Including among them is the state of Indonesia. Where Indonesia is slowly but surely increasing the number of victims from both ordinary people and medical personnel. The mortality ratio is 8%. Some of the deaths were due to Covid-19 medical personnel. The ratio of the death rate due to Covid 19 in Indonesia is recorded as the highest in the Southeast Asia region. Medical personnel are a profession where handling Covid-19 is at the forefront. However, the Indonesian government has not been able to meet the needs of medical personnel in order to serve or treat positive COVID-19 patients. Several government referral hospitals for covid-19 patients do not yet have sufficient medical equipment such as PPE, N95 Mask, Hand Sanitazer and others. This of course is not in accordance with Law Number 36 of 2014 concerning health workers. The research method used in this article is a normative research approach with a statute approach. The purpose of writing this scientific article is to provide recommendations regarding the government's responsibility for the rights of medical personnel as stipulated in Law Number 36 of 2004 concerning Health Workers.Keywords: Health Workers, Covid-19, Legal Protection